1997
DOI: 10.1002/art.1780400115
|View full text |Cite
|
Sign up to set email alerts
|

Similarities of specificity and cofactor dependence in serum antiphospholipid antibodies from patients with human parvovirus B19 infection and from those with systemic lupus erythematosus

Abstract: Objective. To assess the phospholipid specificity and immunoglobulin isotype of antiphospholipid (aPL) antibodies in patients with acute parvovirus B19 infection.Methods. Specificity of aPL and isotype distribution in the negatively charged phospholipids, cardiolipin and phosphatidyl serine, and in the neutral phospholipid, phosphatidyl ethanolamine, were measured in the sera of patients with acute parvovirus B19 infections (n = 12), in those with other acute viral infections (n = lo), and in those with syphil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
62
0

Year Published

1998
1998
2010
2010

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 130 publications
(62 citation statements)
references
References 14 publications
0
62
0
Order By: Relevance
“…Hojnik et al (30) found increased levels of anti-β2GPI Ab's in a significant proportion of leprotic patients, an observation that was confirmed by other investigators who indicated that these β2GPI-dependent aPLs were associated with thrombosis in leprosy (31). In another study, parvovirus B19-associated aCL Ab's were shown to be β2GPI dependent and behaved in a fashion similar to the autoimmune aPLs (32). Furthermore, some cases of viral hepatitis C-associated aPLs have been reported to be complicated with thrombosis (33).…”
Section: Discussionmentioning
confidence: 72%
“…Hojnik et al (30) found increased levels of anti-β2GPI Ab's in a significant proportion of leprotic patients, an observation that was confirmed by other investigators who indicated that these β2GPI-dependent aPLs were associated with thrombosis in leprosy (31). In another study, parvovirus B19-associated aCL Ab's were shown to be β2GPI dependent and behaved in a fashion similar to the autoimmune aPLs (32). Furthermore, some cases of viral hepatitis C-associated aPLs have been reported to be complicated with thrombosis (33).…”
Section: Discussionmentioning
confidence: 72%
“…Other investigators have shown that these ␤ 2 GPI-dependent aPL were associated with thrombosis in leprosy (53). In another study, parvovirus B19-associated aCL antibodies were shown to be ␤ 2 GPI dependent and to behave in a manner similar to that of "autoimmune" aPL (51). Furthermore, some cases of viral hepatitis C-associated aPL have been reported to be complicated with thrombosis (48).…”
Section: Discussionmentioning
confidence: 95%
“…Recently, the belief that infection-associated aPL are ␤ 2 GPI-independent, do not bind ␤ 2 GPI in the absence of phospholipids, and are not associated with thrombosis or other clinical complications of APS has been challenged in a significant number of reports (50)(51)(52). In one study, aCL present in leprosy patients were shown to be heterogeneous with respect to their ␤ 2 GPI requirement: in 10 of 31 leprosy sera, the aCL were ␤ 2 GPI dependent, and 21 of 31 did not require ␤ 2 GPI for binding to CL (50).…”
Section: Discussionmentioning
confidence: 99%
“…Some studies, however, have indicated that antibodies against ␤2GPI can also be found in patients with parvovirus B19, leptospirosis, syphilis, and other infections (25)(26)(27). Because these patients did not show clinical signs of APS, the specificity of anti-␤2GPI detection by ELISA is questionable.…”
Section: Discussionmentioning
confidence: 99%